Reflection on the Statutory Auditor since Phenomenological sociology from Alfred Schütz (2019)
This article seeks to make a reflection about the fiscal audit, taking as a reference the socio-phenomenological theory of the Austrian Alfred Schütz; which analyzes, among other categories, relations of othernes sin the world of everyday life; world that characterizes as the reality primary or fundamental, because in this communication, the action and the inter-subjectivity. Intersubjectivity is per from the space-time matrix, which determines when a relationship over time and space is shared, the relationship takes the character face (Privacy) and only when shared space, the relationship occurs between contemporary (anonymous). This conception of social relations is taken to the Organization to: 1. establish that the organizational structure, with an emphasis on the bureaucratic structure, intentionally defines which member’s summit will or no privacy or anonymity and 2. to have much of the autonomy of the Fiscal Reviewer problems to do with the way how the organizational structure determines the relations of otherness. The Prosecutor Reviewer is in continuous questioning for his little independence to comply with the rules laid down by the State. From the perspective of phenomenological sociology, the problem is in the way of realizing the relations of otherness and everyday life in organizations.